Diqqah at-Tarjamah al-Isti’ârah at-Tashrîhiyyah li Wizârah as-Syuûn ad-Dîniyyah wa Hamka - Uyuni, Yuyun Rohmatul (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
This study aims to determine the accuracy of the technique and meaning in translating isti’ârah tashrîhiyah in “The Quran and its Translation” the work of Kemenag RI and “Tafsir al-Azhar” the work of HAMKA. This research is urgent to be carried out, because it can make a contribution as a referral understanding of Alquran; as a subject matter translation of Alquran; as a research for advanced research. The method used in this research is descriptive-qualitative, the depiction on data logically by using content analysis. The content analysis is an attempt to understand the text content of the text provided by the author. The source of this analyzed data is derived from “Alquran dan Terjemahnya” and “Tafsir al-Azhar”. While the research instrument is the research himself as the central actor. The techniques of data analysis to answer the research questions posed are: indentification, description, interpretation, comparison, correction and conclusions. The result of this research are: Translating isti’ârah tashrîhiyah that is in accordance with the principals of balaghah and opinions of the commentators in the translation book of Kemenag RI as much as 27, 14%, while the translating that is not in accordance with them as much as 52.87%. Translating isti’ârah tashrîhiyah that is in accordance with the concept of balaghah and opinions of the commentators in the translation book of HAMKA as much as of 21.43%, while the translating that is not in accordance with them as much as 78.57%. This research showed that learning translation of the Alquran must be started from the easiest techniques to the most difficult. Their sequence is correspondence, then description, and then integration in accordance with the level of difficult clauses. The accuracy of translation must be refered to principals of balaghah and opinions of commentators.